Ghost fishing impacts on hydrocorals and associated reef fish assemblages. (October 2020) - Beneli, T.M.; Pereira, P.H.C.; Nunes, J.A.C.C.; Barros, F.
Abstract: Ghost fishing is a threat to many marine environments, as lost or discarded fishing gear (e.g., fishing lines, nets) continues to fish by entangling, damaging or killing various organisms. Among the benthic organisms that live on tropical reefs, the group probably most affected, due to their shape, are the branching corals. These corals provide refuge, foraging and breeding sites, especially for fishes and therefore impacts on coral structure could compromise the ecology of associated species. We tested if fishing lines entangled on the branching coral Millepora alcicornis would result in an increase in colony mortality, decrease in abundance and richness of fishes and changes in the behavior of associated reef fish. In the field, we estimated the volume of M. alcicornis colonies and its mortality percentages, and videos were recorded to evaluate abundance and richness of fish assemblages and fish behavior. Our results showed that coral mortality increased with increasing amounts of entangled fishing lines. Fish assemblages were similar in M. alcicornis colonies with or without entangled fishing lines. Nevertheless, we observed a significant decrease in the frequency of feeding attempts in two herbivore fish species ( Acanthurus bahianus and Ophioblennius trinitatis ) that play an important role in coral-reef dynamics, controlling algae abundances. Therefore, ghost fishing has negative impacts on shallow reef ecosystems, directly affecting branching corals and important coral-fish interactions. Management of tropical shallow reef environments should consider regulation and monitoring of coastal fisheries to ensure reef integrity. Highlights: Ghost fishing is a threat to many marine environments. Entangled fishing lines increases mortality of Millepora alcicornis . Herbivore fish species decreases feeding attempts in entangled coral colonies. Ghost fishing impacts coral colonies health and important coral-fish interactions.